Analisis Optimasi Produktivitas Alat Gali-Muat (Excavator) Dan Alat Angkut (Dump Truck) Pada Pengangkutan Andesit Untuk Mengoptimalkan Produksi Di PT. Koto Alam Sejahtera - Afdal Zikri; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT Koto Alam Sejahtera is a private mining company engaged in the andesite mining business in Koto Alam, Lima Puluh Kota Regency. In andesite mining activities, PT. Koto Alam Sejahtera uses a series of excavators and dump trucks to move material from the loading point to the waste dump. In the process of transporting andesite to the crusher there is a queue of dump trucks and long stand-by times at the dump trucks, this can cause the productivity of the tools to be small so that the Andesite stone production target of 80,000 tons / month is not achieved. This is due to the inefficient working time of mechanical tools. This production target was not achieved due to the inappropriate combination of transportation equipment (Mitsubishi Fuso 220 PS) and loading equipment (Hitachi ZX350) which resulted in queues or waiting times for transportation vehicles. One of the ways to achieve the production target requires appropriate fleet management. Based on research that was carried out in October 2019, the productivity of the Hitachi ZX-350 excavator was 344,9378 tons / hour and the productivity of the Mitsubishi Fuso 220 PS dump truck was 78,10247 tons / hour. The composition of the equipment used is 1 unit of excavator serving 5 units of dump trucks, causing the combination of transportation and loading factors to be inappropriate. To overcome the long queue time, the composition of the MF = 1 tool was improved. Fleet settings are based on the queuing method, namely 1 unit of digging equipment and 4 units of transportation equipment with a production of 83.101,03 tons / month. Keywords: Flee Management, Queuing Method, Match Factor, Production, Productivity, Dump Truck